MyosinVa and dynamic actin oppose minus-end directed microtubule motors to drive anterograde melanosome transport - Robinson, Christopher L. (2016)
The intracellular transport of organelles and vesicles is thought to utilise both microtubules and actin filaments, which mediate long and short-range transport, respectively. Melanosomes, synthesised in melanocytes, are a convenient model organelle to study intracellular transport, since they are visible using brightfield microscopy. They are believed to be transported from the perinuclear area to the actin cortex along microtubules, and then captured by the myosin-Va/melanophilin/Rab27a complex which traffics them along actin filaments to the plasma membrane. In contrast, data presented here demonstrate that anterograde melanosome transport relies only upon the actin cytoskeleton. Myosin-Va null melanocytes were used to test the importance of microtubules and actin on long-range organelle transport. In these cells, melanosomes cluster around the perinuclear area, but disperse into peripheral dendrites upon reintroduction of the myosin-Va gene. When this assay was repeated in the absence of microtubules, melanosomes still dispersed indicating that microtubule-based motors are not necessary for long-range anterograde trafficking. However, depolymerising F-actin, or freezing actin dynamics with latrunculin A or jasplakinolide inhibited the dispersion of pigment granules in myosin-Va null cells melanocytes and induced a clustered phenotype in WT melanocytes. This effect was abolished if microtubules were absent, suggesting that microtubules are only required for retrograde transport whilst dynamic actin is essential for anterograde melanosome transport. Moreover, when Kif5B was forcibly recruited to the melanosome membrane via an inducible dimerisation system, the melanosomes dispersed abnormally. An siRNA knockdown screen of over 120 actin binding proteins identified several proteins including formin-1, Arpc1b, cofilin-1, gamma-actin and spire1/2, which appear to be necessary for maintaining peripherally dispersed melanosomes. This evidence further underlines the importance of the actin cytoskeleton, rather than the microtubule network as previously thought, for the anterograde trafficking of melanosomes.